Cost–benefit analysis of intervention reducing young stock mortality in Ethiopia - Kirk, Thomas W. D.; Byrne, Timothy; Bessel, Paul; Vance, Ciara; Schnier, Christian; Peters, Andrew R. (Frontiers in Veterinary Science, 2024)
Livestock provide meat, milk, draught labour, are used for breeding, and act as a store of value for smallholder farmers. High young stock mortality (YSM) has the potential to cause significant financial loss. The Young Stock Mortality Reduction Consortium collaborated on a project to deliver a package of basic health and husbandry interventions to reduce YSM for cattle and small ruminants in mixed and pastoral production systems in Ethiopia. Prior to the intervention, YSM rates ranged from 9.8% for calves in mixed systems, to 35.6% for small ruminants in pastoral systems. Proportional reductions YSM from the intervention ranged from 60% for calves and for small ruminants in mixed systems, to 72% for calves in pastoral systems. This brief research report assesses the costs and benefits of the intervention ex-poste to determine its efficiency.NPVs for the intervention (per household) were calculated for a range of benefit periods (from 1 to 20 years), based on the cost of training enumerators and farmers and the net annual household benefits realised within each benefit period.We found in both pastoral and mixed systems the net annual household benefit for the intervention was positive. For pastoral households the intervention achieves a positive NPV after two years. For mixed households the intervention achieves a positive NPV after 11 years. Overall, we found the benefits of the intervention exceed the costs, by a very large amount in pastoral systems, and that benefits were larger for households that kept larger numbers of breeding females.